Evaluation of the Antiviral Activity of Sephin1 Treatment and Its Consequences on eIF2α Phosphorylation in Response to Viral Infections - Fusade-Boyer, Maxime; Dupré, Gabriel; Bessière, Pierre; Khiar, Samira; Quentin-Froignant, Charlotte; Beck, Cécile; Lecollinet, Sylvie; Rameix-Welti, Marie-Anne; Eléouët, Jean-François; Tangy, Frédéric; Lajoie, Barbora; Bertagnoli, Stéphane; et al. (Frontiers in Immunology, 2019)
The guanabenz derivative Sephin1 has recently been proposed to increase the levels of translation initiation factor 2 (eIF2α) phosphorylation by inhibiting dephosphorylation by the protein phosphatase 1 - GADD34 (PPP1R15A) complex. As phosphorylation of eIF2α by protein kinase R (PKR) is a prominent cellular antiviral pathway, we evaluated the consequences of Sephin1 treatment on virus replication. Our results provide evidence that Sephin1 downregulates replication of human respiratory syncytial virus, measles virus, human adenovirus 5 virus, human enterovirus D68, human cytomegalovirus and rabbit myxoma virus. However, Sephin1 proved to be inactive against influenza virus, as well as against Japanese encephalitis virus. Sephin1 increased the levels of phosphorylated eIF2α in cells exposed to a PKR agonist. By contrast, in virus-infected cells, the levels of phosphorylated eIF2α did not always correlate with the inhibition of virus replication by Sephin1. This work identifies Sephin1 as an antiviral molecule in cell culture against RNA, as well as DNA viruses belonging to phylogenetically distant families.